Effect of Catalyst Layer Ionomer Content on Performance of Intermediate Temperature Proton Exchange Membrane Fuel Cells (IT-PEMFCs) under Reduced Humidity Conditions. (10th January 2017) - Cho, Min Kyung; Park, Hee-Young; Lee, So Young; Lee, Byung-Seok; Kim, Hyoung-Juhn; Henkensmeier, Dirk; Yoo, Sung Jong; Kim, Jin Young; Han, Jonghee; Park, Hyun S.; Sung, Yung-Eun; Jang, Jong Hyun
Abstract: For intermediate-temperature polymer electrolyte membrane fuel cells (IT-PEMFCs), the effects of the cathode gas flow rate and the ionomer content are experimentally examined at 120 °C under conditions of low relative humidity (RH). The IT-PEMFC operation at low RH should be beneficial in developing compact systems with smaller humidifiers. First, analysis of the effect of gas flow rate at various current densities confirms that drying of the membrane electrode assembly (MEA) is an important factor in IT-PEMFC operation, whereas cathode flooding becomes significant in regions of high current density with low flow rates. Then, MEAs with various contents of Aquivion™ ionomer are fabricated, and the combined effect of drying and flooding is further investigated by IT-PEMFC tests at various RH conditions and current densities. The optimum ionomer content increases with decreasing current density at 20% RH or below, indicating that MEA drying becomes dominant over cathode flooding.